Production Planning and Profit Maximization of Furniture Production at PD. Maha Kayu Sejahtera Using Linear Programming Method with LINGO and POM-QM Software - Hakim, Lukmanul (SEAN Institute, 2025)
UMKM is a type of small business that plays an important role in improving and stimulating the local economy. One UMKM engaged in the furniture industry is PD Maha Kayu Sejahtera, located at Jl. Tanjakan Lama, Tanjakan Village, RT05/02, Rajeg District, Tangerang Regency. The Simplex Method is used to ensure the sustainability and growth of the furniture production business, which is part of a linear programming design. The application of the Simplex Method is carried out using software tools such as LINGO and POM-QM. POM-QM, used for modeling and solving linear programming problems, offers advantages in providing an accurate and efficient approach. The maximum profit of products at PD Maha Kayu Sejahtera, based on both manual calculations and software assistance using LINGO and POM-QM, is IDR 8,100,000 per week.